Formulation Development of Directly Compressible Tablets Incorporating Trisamo Extract With Synergistic Antioxidant Activity - Jirapornchai Suksaeree; Thaniya Wunnakup; Natawat Chankana; Laksana Charoenchai; Chaowalit Monton (International Journal of Food Science)
This work investigates the synergistic antioxidant activity of the compositions of Trisamo (TSM) herbal formula containing the dried fruits of Terminalia chebula, Terminalia arjuna, and Terminalia bellirica. An augmented simplex lattice design was utilized to investigate the synergistic antioxidant activity, finding an equal mass ratio among the three herbal drugs to exhibit optimal synergistic antioxidant activity, with a combination index of less than 0.8. The optimal TSM extract was used to prepare directly compressible tablets employing a Box–Behnken design response surface methodology, optimizing compressional force (500, 1000, and 1500 psi), sodium starch glycolate (0%, 2%, and 4%), and magnesium stearate (0.5%, 1.0%, and 1.5%). Optimal parameters were a compressional force of 1000 psi, 2% sodium starch glycolate, and 0.5% magnesium stearate. The TSM extract tablet had a weight of 600.06 mg, a diameter of 12.78 mm, a thickness of 4.12 mm, a hardness of 6.85 kP, a friability of 0.30%, and a disintegration time of 1.81 min. Computer model predictions were verified with a low percentage error (≤ 10.00%). After 6 h, phenolic compounds were dissolved to an extent of approximately 40%–80%, including gallic acid (57.11%), corilagin (38.64%), chebulagic acid (58.49%), and chebulinic acid (81.44%). Stability data revealed that the phenolic compounds were retained for 3 months compared to the initial time point, with gallic acid at 81.43% and 100.27%, corilagin at 94.81% and 87.85%, chebulagic acid at 92.22% and 69.83%, and chebulinic acid at 107.00% and 85.54% at 30°C/75% RH and 45°C/75% RH, respectively. The summation of these four compounds did not change significantly when stored under either set of conditions. In summary, mixture design and response surface design were successfully utilized in the optimization of TSM extract tablets with synergistic antioxidant activity.